At Westonci.ca, we connect you with the best answers from a community of experienced and knowledgeable individuals. Get accurate and detailed answers to your questions from a dedicated community of experts on our Q&A platform. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.

please help me with this question.

Please Hurry​


Please Help Me With This QuestionPlease Hurry class=

Sagot :

Answer:

cos 2θ + cos θ = (2cos θ - 1)(cos θ + 1)

cos 2θ - cos θ = (2cos θ + 1)(cos θ - 1)

Step-by-step explanation:

cos 2θ + cos θ = 2cos²θ - 1 + cos θ      

cos 2θ + cos θ = 2cos²θ + cos θ - 1

                           2cos θ               - 1

                             cos θ              + 1

cos 2θ + cos θ = (2cos θ - 1)(cos θ + 1)

cos 2θ - cos θ = 2cos²θ - 1 - cos θ      

cos 2θ - cos θ = 2cos²θ - cos θ - 1

                           2cos θ             + 1

                             cos θ              - 1

cos 2θ - cos θ = (2cos θ + 1)(cos θ - 1)